A Case of Childhood Blastic Phase Chronic Myeloid Leukemia With Minor BCR-ABL. Issue 6 (August 2020) - Yamanaka, Junko; Shimizu, Mariko; Sato, Maho; Inoue, Masami; Matsui, Motohiro; Shimada, Hiroyuki; Shichino, Hiroyuki
Abstract : Chronic myeloid leukemia (CML) is commonly associated with major BCR-ABL transcript. We present a child with blastic phase CML associated with minor BCR-ABL transcript without prior CML diagnosis. Diagnosis was achieved by fluorescence in situ hybridization of peripheral blood neutrophils, which identified 90% as BCR-ABL positive. The patient received chemotherapy with imatinib followed by dasatinib and underwent reduced-intensity hematopoietic allogeneic stem cell transplantation with prophylactic posttransplant dasatinib for 2 years and has remained in complete molecular remission. Our intensified treatment regimen was effective compared with previous studies on minor BCR-ABL CML describing inferior outcomes with tyrosine kinase inhibitor therapy.